Reliability of the [13C]‐acetate breath test in the measurement of gastric emptying of ethanol solutions: a methodological study - Franke, Andreas; Harder, Hermann; Singer, Manfred V. (Scandinavian journal of gastroenterology, 2004)
Background: The [ 13 C]‐acetate breath test is a clinically well‐established test for measuring gastric emptying of liquids and correlates significantly with scintigraphy. However, no studies have been undertaken to examine the relationship between gastric emptying measured by the [ 13 C]‐acetate breath test and ultrasonography. Furthermore, it is not known how ethanol may affect gastric emptying as measured by the [ 13 C]‐acetate breath test. This is particularly important because of the additional steps of absorption, metabolism and exhalation of the tracer involved in the [ 13 C]‐acetate breath test compared to the simple measurement of gastric emptying by ultrasonography. The aim of the present study was to examine the relationship between the gastric half emptying times measured by the [ 13 C]‐acetate breath test and by ultrasonography and to determine the effect of ethanol on the comparability between both methods. Methods: On separate days, 10 healthy, fasted randomly selected subjects received the following solutions by gastric tube: 500 mL water, 4% and 10% (v/v) ethanol, 5.5% and 11.4 % (w/v) glucose. Gastric half emptying times of the test solutions were simultaneously determined using the [ 13 C]‐acetate breath test and ultrasonography of the fundus and the antrum. Results: The gastric emptying rates determined by ultrasonography of the fundus correlated significantly with the results obtained using the [ 13 C]‐acetate breath test for all test solutions (r = 0.64-0.92, P < 0.05 for all), whereas ultrasonography of the antrum correlated significantly with the breath test only when water (r = 0.94, P = 0.001) was used. The difference between the mean half‐emptying times obtained using the [ 13 C]‐acetate breath test and ultrasonography of the fundus was 55 ± 1.8 min. This difference was significantly longer when 4% and 10% (v/v) ethanol solutions were given (61.2 ± 3.3 and 71.2 ± 2.9 min) compared to water (P < 0.05). Conclusions: A good correlation was found between gastric emptying as measured by the [ 13 C]‐acetate breath test and ultrasonography of the fundus. Measurements that were obtained using the [ 13 C]‐acetate breath test demonstrate a longer gastric half emptying time compared with those obtained using ultrasonography. This difference is even more marked when ethanol solutions are used. Presumably, this is because ethanol affects the absorption and/or the hepatic metabolism of the tracer. The [ 13 C]‐acetate breath test is therefore not a reliable gastric emptying test for comparison of different solutions, especially when ethanol‐containing liquids are used.
Im Text ist "13" hochgestellt
Published online: 08 Jul 2009
Gesehen am 29.04.2022